2004
DOI: 10.1182/blood-2003-09-3287
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in PTPN11 implicate the SHP-2 phosphatase in leukemogenesis

Abstract: The PTPN11 gene encodes SHP-2 (Src homology 2 domain-containing protein tyrosine Phosphatase), a nonreceptor tyrosine protein tyrosine phosphatase (PTPase) that relays signals from activated growth factor receptors to p21 Ras (Ras) and other signaling molecules. Mutations in PTPN11 cause Noonan syndrome (NS), a developmental disorder characterized by cardiac and skeletal defects. NS is also associated with a spectrum of hematologic disorders, including juvenile myelomonocytic leukemia (JMML). To test the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
316
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(343 citation statements)
references
References 55 publications
23
316
1
3
Order By: Relevance
“…It is more likely that missing interaction with other signal transduction molecules (e.g. c-Cbl) could explain the absence of ERK inhibition in this case, especially as inhibition is observed with the catalytic inactive SHP-2 C>S. The finding that constitutive activation of SHP-2 does not necessarily lead to increased ERK activation has been described earlier in other cell types [40,41]. In "knockin" mice of constitutive active SHP-2 the authors observed increased ERK phosphorylation only in specific cell types in approximately 50% of the mutant mice [40].…”
Section: Discussionsupporting
confidence: 57%
“…It is more likely that missing interaction with other signal transduction molecules (e.g. c-Cbl) could explain the absence of ERK inhibition in this case, especially as inhibition is observed with the catalytic inactive SHP-2 C>S. The finding that constitutive activation of SHP-2 does not necessarily lead to increased ERK activation has been described earlier in other cell types [40,41]. In "knockin" mice of constitutive active SHP-2 the authors observed increased ERK phosphorylation only in specific cell types in approximately 50% of the mutant mice [40].…”
Section: Discussionsupporting
confidence: 57%
“…Noonan syndrome is also associated with increased risk of juvenile myelomonocytic leukemia (JMML) (Choong et al, 1999), suggesting the role of mutant SHP-2 in leukemogenesis. Indeed, somatic mutations in PTPN11 occur in 35% cases of JMML, 4% of childhood acute myelocytic leukemias and 7% of childhood B-cell acute lymphoblastic leukemias (Tartaglia et al, 2003(Tartaglia et al, , 2004Loh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…55,56 Somatic mutations in PTPN11 represent the most frequent molecular lesion identified to date in JMML, with up to 35% of JMML cases demonstrating PTPN11 mutations, often mutually exclusive with RAS or NF1 mutations. [57][58][59][60][61] Mouse models of these genetic lesions have proven their causal role in myeloproliferative disease development as well as hyperactivation of the Ras pathway and GM-CSF hypersensitivity. [62][63][64][65][66][67] The interested reader can see one of several recent reviews for a more in-depth review of these biochemical and genetic aberrations.…”
Section: Jmmlfpathogenesismentioning
confidence: 99%